AVIATION ENGLISH TEST DEVELOPMENT - Petrashchuk, Olena (Proceedings of National Aviation University (archive), 2014)
The article highlights the English language test development for the purposes of English language proficiency assessment against the ICAO Rating scale. The procedure of the test construction is described on the example of the Test of English for Aviation Personnel developed in 2007 in Ukraine.